2021
DOI: 10.3389/fncir.2021.709387
|View full text |Cite
|
Sign up to set email alerts
|

α3β4∗ Nicotinic Acetylcholine Receptors Strongly Modulate the Excitability of VIP Neurons in the Mouse Inferior Colliculus

Abstract: The inferior colliculus (IC), the midbrain hub of the central auditory system, receives extensive cholinergic input from the pontomesencephalic tegmentum. Activation of nicotinic acetylcholine receptors (nAChRs) in the IC can alter acoustic processing and enhance auditory task performance. However, how nAChRs affect the excitability of specific classes of IC neurons remains unknown. Recently, we identified vasoactive intestinal peptide (VIP) neurons as a distinct class of glutamatergic principal neurons in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 84 publications
(129 reference statements)
3
11
0
Order By: Relevance
“…Thus, in a minority of VIP neurons, the α 3 subunit presumably forms functional nAChRs by pairing with non-β 4 subunits. This extends the interpretation of our recent pharmacological study, which showed that cholinergic responses in VIP neurons were largely blocked by SR16584 (Rivera-Perez et al 2021), an antagonist reported to be selective for α 3 β 4 * nAChRs (Zaveri et al 2010). A likely explanation is that SR16584 blocks not only α 3 β 4 * nAChRs but also other α 3 -containing nAChRs.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Thus, in a minority of VIP neurons, the α 3 subunit presumably forms functional nAChRs by pairing with non-β 4 subunits. This extends the interpretation of our recent pharmacological study, which showed that cholinergic responses in VIP neurons were largely blocked by SR16584 (Rivera-Perez et al 2021), an antagonist reported to be selective for α 3 β 4 * nAChRs (Zaveri et al 2010). A likely explanation is that SR16584 blocks not only α 3 β 4 * nAChRs but also other α 3 -containing nAChRs.…”
Section: Discussionsupporting
confidence: 86%
“…Although α 3 and β 4 nAChR subunits have limited expression in the brain, radioligand-binding and in situ-hybridization studies indicate that the IC is one of the few brain regions where these subunits are expressed (Wada et al 1989; Whiteaker et al 2002; Marks et al 2002; Salas et al 2003; Gahring et al 2004; Marks et al 2006). Consistent with this, we recently found that excitation of VIP neurons by acetylcholine is largely blocked by SR16584, an antagonist selective for α 3 β 4 * nAChRs (Rivera-Perez et al 2021). Since the specificity of receptor antagonists is rarely perfect, especially for antagonists against receptors that can exist in many heteromeric combinations, we tested whether these pharmacological results were supported by the expression of α 3 and β 4 subunits in VIP neurons.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations